2003
DOI: 10.1086/377046
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Influenza Virus Load by Real‐Time Polymerase Chain Reaction in Nasopharyngeal Swabs of Patients Treated with Oseltamivir

Abstract: Influenza A virus load was assessed by real-time polymerase chain reaction (PCR) in nasopharyngeal swabs of infected patients treated with oseltamivir. The mean pretreatment virus load was significantly lower in the 24 patients (group A) who initiated treatment within 24 h of the onset of symptoms than it was in the 26 patients (group B) who initiated treatment between 24 and 48 h (1.6x105 vs. 8.4x105 copies/600 ng of total RNA, P=.04); after 48 h of treatment, twice as many patients in group B still had a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 12 publications
4
24
1
1
Order By: Relevance
“…2 to 6. Based upon the reported mass of an influenza virus particle of 5 femtograms or 5 ϫ 10 Ϫ16 g (21), this corresponds to ϳ10 5 copies of the virus, a value comparable to that reported for the RT-PCR analysis of virus obtained from nasopharyngeal swabs (22).…”
Section: Resultssupporting
confidence: 61%
“…2 to 6. Based upon the reported mass of an influenza virus particle of 5 femtograms or 5 ϫ 10 Ϫ16 g (21), this corresponds to ϳ10 5 copies of the virus, a value comparable to that reported for the RT-PCR analysis of virus obtained from nasopharyngeal swabs (22).…”
Section: Resultssupporting
confidence: 61%
“…The results of a multi-centre international study have recently confirmed the expectation that early treatment with oseltamivir significantly reduces the total duration of illness more effectively than does delayed treatment [13]. This is consistent with studies showing more rapid control of influenza viral load in patients given oseltamivir within the first 24 hours of illness onset [14]. Since these drugs effectively suppress viral replication, they should not, of course, be given to individuals who have recently received live attenuated vaccine, further illustrating the need for a two stage vaccine/drugs approach to controlling influenza.…”
supporting
confidence: 73%
“…Moreover, negative PCR results were achieved more rapidly if the treatment was initiated within the first 24 h (n = 24) of onset of symptoms than after 24 h of symptom onset (n = 26). 37 In contrast to these studies, in a placebo-controlled trial in 629 adults, treatment with oseltamivir 75 mg or 150 mg BID had no significant effect on virus shedding and titers (Table 3) in naturally acquired influenza A infections. 33 There are limited data on the effects of treatment with zanamivir on viral shedding.…”
Section: Treatment Studiesmentioning
confidence: 90%